(untitled) (Metallurgy and Foundry Engineering, 2019)
The effect of the initial texture on the deformation mode and mechanical properties was studied in magnesium and its AZ61 alloy. Both materials had a very similar initial texture. Two cases were investigated: samples with a texture where the basal slip system was blocked, and samples having a texture where the basal slip system was allowed to activate. The samples were deformed by compression at room temperature at a strain rate of 10-3 s-1. It was found that the initial texture had a very strong impact on the deformation mode in magnesium; however, there was no effect of the initial texture on the deformation mode in the case of AZ61. The investigations were compared to simulations of texture evolution using the Taylor model. From the simulations, the Taylor factor and slip system activity were obtained. It was found that, in the case of magnesium, twinning or slip (both basal and non-basal) are the two main deformation modes, while in the case of AZ61, slip is the only main deformation mechanism despite the initial texture. The impact of the initial texture is discussed in more detail in the present study.